EQUAÇÕES EXPONENCIAIS

Exercícios Resolvidos 𝑎

) 2𝑥+1 = 23 ⇒ 𝑥 + 1 = 3 ∴ 𝑥 = 2 𝑏
) 5𝑥

2 +2𝑥

= 53 ⇒ 𝑥 2 + 2𝑥 = 3 𝑥
2 + 2𝑥 − 3 = 0 ∴ 𝑥 = −3 𝑜𝑢 𝑥 = 1 𝑐

) 34−2𝑥 = 32

2𝑥

34−2𝑥 = 34𝑥 ⇒ 4 − 2𝑥 = 4𝑥

4
2
4 = 6𝑥 ∴ 𝑥 =
=
6
3 𝑑

) 22 𝑥

= 23

22𝑥

23 𝑒

) 23

= 𝑥

+1

3
⇒ 2𝑥 = 3 ∴ 𝑥 =
2

= 25

23𝑥+3 = 25 ⇒ 3𝑥 + 3 = 5
3𝑥 = 2

∴𝑥=

2
3 𝑓

) 3𝑥

2 +𝑥

= 32 ⇒ 𝑥 2 + 𝑥 = 2 𝑥
2 + 𝑥 − 2 = 0 ∴ 𝑥 = −2 𝑜𝑢 𝑥 = 1 𝑔

) 3𝑥 = 34 ⇒ 𝑥 = 4 𝑕
) 2𝑥−3 = 24 ⇒ 𝑥 − 3 = 4 ∴ 𝑥 = 7 𝑖
) 4𝑥 = 43 ⇒ 𝑥 = 3 𝑗
) 2𝑥+1 = 20 ⇒ 𝑥 + 1 = 0 ∴ 𝑥 = −1 𝑘
) 23 𝑥

+1

= 27 𝑥

−3

23𝑥+3 = 27𝑥−21 ⇒ 3𝑥 + 3 = 7𝑥 − 21
21 + 3 = 7𝑥 − 3𝑥
4𝑥 = 24 ∴ 𝑥 = 6 𝑙
) 25𝑥+2 = 250 ⇒ 𝑥 + 2 = 0 ∴ 𝑥 = −2 𝑎

) 4−1 𝑥

−2

= 42 𝑥

4−𝑥+2 = 42𝑥 ⇒ −𝑥 + 2 = 2𝑥 𝑏

) 34 𝑥

2 −𝑥

34𝑥

= 3−3

2 −4𝑥

2
2 = 3𝑥 ∴ 𝑥 =
3

−8

= 324 ⇒ 4𝑥 2 − 4𝑥 = 24
4𝑥 2 − 4𝑥 − 24 = 0 𝑥
2 − 𝑥 − 6 = 0 ∴ 𝑥 = −2 𝑜𝑢 𝑥 = 3

2 𝑐

) 10 𝑥 = 104 ⇒ 𝑥 2 = 4 ∴ 𝑥 = ± 4 = ±2 𝑑
) 2𝑥 = 2−5 ⇒ 𝑥 = −5 𝑒
) 32 𝑥

= 3−1

32𝑥 = 3−1 ⇒ 2𝑥 = −1 ∴ 𝑥 = − 𝑓
) 5𝑥 = 5−4

⇒ 𝑥 = −4

1
2 𝑎

)

2 𝑥

51
1

5

2

= 53 𝑥

= 53 𝑥

=3 ∴ 𝑥=6
=5 ⇒
2 𝑥

52

3

2 𝑏

) 6𝑥 = 62 𝑥

62 𝑒

) 25 𝑥

+3

=

3

1

25𝑥+15 = 2

= 66 ⇒

21 𝑐

) 5𝑥 =

3

5𝑥

1
5𝑥 + 15 =
3

15𝑥 = −44 ∴ 𝑥 = −

44
15

2𝑥

7

2

=5 𝑑

) 72

15𝑥 + 45 = 1

3 𝑥

51

1

=

=7 𝑥

= 6 ∴ 𝑥 = 12
2

2

⇒ 𝑥=

2

71

1

2

1
2

⇒ 2𝑥 =

1
1
∴ 𝑥=
4
2 𝑎

)

4𝑥

. 41

4𝑥
− 1 = 60
4 𝑥

4
4𝑥 . 4 −
= 60
4

4𝑥 = 𝑦

4𝑥 = 16 𝑦

4𝑦 − = 60
4

4𝑥 = 42

16𝑦 − 𝑦 = 60 × 4
15𝑦 = 60 × 4
4 𝑦

=

60 × 4
15
1 𝑦

= 16

∴ 𝑥=2

5𝑥 5𝑥 𝑏
) 1 + 2 = 6
5
5
5𝑥 5𝑥
+
=6
5 25

5𝑥 = 25

5𝑥 = 𝑦 𝑦 𝑦

+
=6
5 25
5𝑦 + 𝑦 = 6 × 25

6𝑦 = 6 × 25
1

1 𝑦

= 25

5𝑥 = 52
∴ 𝑥=2 𝑐

) 3𝑥 . 31 + 3𝑥 = 36
3𝑥 . 3 + 3𝑥 = 36
3𝑥 = 𝑦
3𝑦 + 𝑦 = 36
4𝑦 = 36 𝑦
=9


3𝑥 = 9
3𝑥 = 32
∴ 𝑥=2 𝑥

7 𝑑
) 7𝑥 . 71 − 49 . 2 = 42
7 𝑥

7
7𝑥 . 7 − 49 .
= 42
49

7𝑥 = 𝑦
7𝑦 − 𝑦 = 42
6𝑦 = 42 𝑦
=7


7𝑥 = 7
7𝑥 = 71
∴ 𝑥=1 𝑒

) 3𝑥 . 31 + 3𝑥 . 32 = 12
3𝑥 = 𝑦
3𝑦 + 9𝑦 = 12
12𝑦 = 12 𝑦
=1


3𝑥 = 1
3𝑥 = 30
∴ 𝑥=0 𝑎

) 22 𝑥

− 6. 2𝑥 + 8 = 0 𝑏

) 52 𝑥

− 2. 5𝑥 + 1 = 0

2𝑥

2

− 6. 2𝑥 + 8 = 0

5𝑥

2

− 2. 5𝑥 + 1 = 0

2𝑥 = 𝑦

5𝑥 = 𝑦 𝑦

2 − 6𝑦 + 8 = 0 𝑦

2 − 2𝑦 + 1 = 0 𝑦

= 2 𝑜𝑢 𝑦 = 4 𝑦

=1 𝑆𝑒

𝑦 = 2 ⇒ 2𝑥 = 2 ∴ 𝑥 = 1 𝑆𝑒
𝑦 = 4 ⇒ 2𝑥 = 4 ∴ 𝑥 = 2 𝑅𝑒𝑠𝑝𝑜𝑠𝑡𝑎

: 𝑥 = 1 𝑜𝑢 𝑥 = 2 𝑦

= 1 ⇒ 5𝑥 = 1

∴ 𝑥=0 𝑅𝑒𝑠𝑝𝑜𝑠𝑡𝑎

: 𝑥 = 0 𝑐

)

32 𝑥
3𝑥 2

3𝑥
+ 3 . 1 = 12
3

3𝑥
+ 3 . − 12 = 0
3
3𝑥 = 𝑦 𝑦

2 + 𝑦 − 12 = 0 𝑑

) 22 𝑥

− 3. 2𝑥 + 2 = 0

2𝑥

2

− 3. 2𝑥 + 2 = 0
2𝑥 = 𝑦 𝑦

2 − 3𝑦 + 2 = 0 𝑦
= 1 𝑜𝑢 𝑦 = 2 𝑦

= −4 𝑜𝑢 𝑦 = 3 𝑆𝑒
𝑦 = −4 ⇒

3𝑥

= −4 ∴ ∄ 𝑥 ∈ ℝ 𝑆𝑒

𝑦 = 3 ⇒ 3𝑥 = 3 ∴ 𝑥 = 1 𝑅𝑒𝑠𝑝𝑜𝑠𝑡𝑎
: 𝑥 = 1 𝑆𝑒

𝑦 = 1 ⇒ 2𝑥 = 1 ∴ 𝑥 = 0 𝑆𝑒
𝑦 = 2 ⇒ 2𝑥 = 2 ∴ 𝑥 = 1 𝑅𝑒𝑠𝑝𝑜𝑠𝑡𝑎

: 𝑥 = 0 𝑜𝑢 𝑥 = 1

3𝑥

2 −3𝑥

= 3−2 ⇒ 𝑥 2 − 3𝑥 = −2 𝑥
2 − 3𝑥 + 2 = 0 ∴ 𝑥 = 1 𝑜𝑢 𝑥 = 2

2𝑥 − 2𝑥 . 21 + 8 = 0
2𝑥 = 𝑦 𝑦
− 2𝑦 = −8
−𝑦 = −8 ∴ 𝑦 = 8

2𝑥 = 8

⇒ 2 𝑥 = 23 ∴ 𝑥 = 3

1

2

2𝑥+1 𝑥
+1
2 2

25
=
100
= 𝑥

+1
2 2

4

1
1
= 2 = 2−2
4
2
=

2−2 𝑥

+1

= −2
2 𝑥
+ 1 = −4 𝑥
= −5

2𝑥 . 22 𝑥

+1

. 23 𝑥

+2

= 24 𝑥

+3

2𝑥 . 22𝑥+2 . 23𝑥+6 = 24𝑥+12
2𝑥+2𝑥+2+3𝑥+6 = 24𝑥+12
26𝑥+8 = 24𝑥+12 ⇒ 6𝑥 + 8 = 4𝑥 + 12
2𝑥 = 4 ∴ 𝑥 = 2

2𝑥+3 . 16 =

2

641

2𝑥+3 . 16 = 8
1

2𝑥+3 =

8
16

2

1
= 2−1
=
2

2𝑥+3 = 2−1 ⇒ 𝑥 + 3 = −1
∴ 𝑥 = −4

22 𝑥

= 25

22𝑥 = 25 ⇒ 2𝑥 = 5 ∴ 𝑥 = 2,5

45
2𝑥

72

2−𝑥

= 25 ⇒

45
=5 ∴ 𝑥=9 𝑥

= 7−1

74−2𝑥 = 7−1

⇒ 4 − 2𝑥 = −1
4 + 1 = 2𝑥

2𝑥 = 5 ∴ 𝑥 = 2,5

ISERJ – 2012
Professora Telma Castro Silva
Fonte: http://blog.educacional.com.br/mjustina/

Sign up to vote on this title
UsefulNot useful